Rethinking Urban Design: Architectural Approaches to Walkability and Sprawl - Savvy Jain (International Journal of Urban Design and Development, 2025)
As cities stretch their concrete fingers across the landscape, architecture stands as both the problem and the solution. Like a master chess player, thoughtful architecture can reshape urban spaces, transforming car-centric sprawl into pedestrian-friendly havens. By crafting inviting streetscapes and mixed-use developments, architects weave a tapestry of walkable neighborhoods that pulse with life and connection. Streetscapes designed with wide sidewalks, pedestrian crossings, green spaces, and appropriate lighting further enhance the walking experience, contributing to a healthier and more vibrant community life. This study examines the critical role of architectural design in promoting walkability and mitigating urban sprawl in contemporary cities. This research investigates how thoughtful architectural interventions can contribute to creating more compact, pedestrian-friendly urban environments. The study employs a mixed-methods approach, combining quantitative analysis of urban form metrics with qualitative case studies of successful walkable neighborhoods. Key architectural strategies explored include mixed-use developments, human-scale design, active frontages, and the integration of green spaces. The research also considers how these design principles interact with broader urban planning policies and transportation infrastructure. The conclusions offer practical insights for architects, urban planners, and policymakers seeking to create more livable, sustainable cities in the face of rapid urbanization.
Keywords: Architecture; mix-use place making; pedestrian-friendly environments; urban density; walkability